Evaluation of automated hematology analyzer DYMIND DH76 compared to SYSMEX XN 1000 system: Analytical performance evaluation of DYMIND DH76 - Velizarova, Milena; Yacheva, Teodora; Genova, Mariana; Svinarov, Dobrin (Journal of Medical Biochemistry, 2021)
Background: DYMIND DH76 (DYMIND BIOTECH, China) is a new automated hematology system designed to provide CBC count, including 5-part WBC differential count, and its analytical performance should be assessed before adoption for clinical use.Methods: The analyzer was evaluated according to the International council for standardization in hematology guideline. The purposes of this study were to assess its analytical performance in comparison to SYSMEX XN 1000 hematology analyzer currently used in our laboratory, as well as a comparison between automated and manual WBC differential.Results: Within-run precision in all concentration ranges was very good with coefficients of variation (CVs) between 0.02% and 2.5% except for platelets over 500×109/L (CV 9.5%). Within-batch imprecision showed CVs lower the declared deviation ranges. Accuracy (defined as trueness) was excellent for all CBC and white cell differential parameters, compared with the state of the art%. Linearity was confirmed with excellent regression coefficients (0.999-1.000), even in the lowest values, and carryover was ≤ 1%. Comparison between DYMIND DH76 and SYSMEX XN 1000 also was very good with correlation coefficients (R2) for WBC (1.000), RBC (0.999), hemoglobin (0.999) and PLT over 50x109/L (0.994) and R2 was lower but still acceptable (0.910) for PLT